2020
DOI: 10.1111/1471-0528.16147
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific reference ranges of serum anti‐müllerian hormone in healthy women and its application in diagnosis of polycystic ovary syndrome: a population study

Abstract: Objective To establish the age‐specific centiles of serum anti‐müllerian hormone (AMH) levels in Chinese women, and to explore the use of multiples of median (MoM) AMH levels for the diagnosis of polycystic ovary syndrome (PCOS). Design An observational study. Setting University‐affiliated hospitals and community clinics. Population We included 3137 healthy women aged 20–44 years recruited prospectively or who had archived serum samples from previous research projects. Another validation cohort of 751 women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
0
22
0
2
Order By: Relevance
“…Meanwhile, the diagnostic performance of AMH for PCOS with age‐group‐specific reference limits was not entirely satisfactory. Additionally, the age‐specific reference limits reported in previous studies 9,10 and the age‐group‐specific reference limits suggested by the assay manufacturer also only offered limited performance for our study population (Table 3). This may be due to overlaps in the distribution of AMH concentrations from healthy women and PCOS patients in the Korean sample population.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Meanwhile, the diagnostic performance of AMH for PCOS with age‐group‐specific reference limits was not entirely satisfactory. Additionally, the age‐specific reference limits reported in previous studies 9,10 and the age‐group‐specific reference limits suggested by the assay manufacturer also only offered limited performance for our study population (Table 3). This may be due to overlaps in the distribution of AMH concentrations from healthy women and PCOS patients in the Korean sample population.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it could be more appropriate to use multiple age‐related cutoff values instead of a universal cutoff as a diagnostic threshold. Previous studies have reported that age‐specific reference limits or multiples of the median (MoM) can significantly increase the diagnostic utility of AMH 9,10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 35 In addition, AMH varies for different ages, so the set of year-by-year age-specific reference ranges of serum AMH levels in Chinese women could be a good reference. 36 The participants need to undergo transvaginal ultrasound in our study, so women who were virgins were not included in our study.…”
Section: Commentsmentioning
confidence: 99%